1992
DOI: 10.1007/bf00124939
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the association of race and ethnicity with the HIV/AIDS-related attitudes, behaviors and skills of high school students

Abstract: This study deals with intervening factors such as family composition, religiosity, and I/IV/AIDS knowledge in understanding the association of race and ethnicity with HIV/A1DS-related attitudes and behaviors. Data represent Wave 1 of a five-month panel design involving 10th grade students in eight public high schools in Dade County (greater Miami) Florida. Significant differences in attitudes and behaviors were found among racial/ethnic groups. Specifically, Hispanics had more negative attitudes about condom u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Other studies using different methodologies show that having a religion influences opinions and experiences with sexuality [38][39][40][41][42] . These findings are similar to the results of our study, which show that greater frequency of participation in religious activities decreased the likelihood of sexual initiation at high school 37,[43][44][45][46][47][48][49][50] . Studies conducted in Africa have shown the opposite -that religiosity may actually increase the likelihood of sexual initiation at high school 51,52 -or that there was no association between religion and sexual initiation 53,54 .…”
Section: Discussion: Will Religious Discourse and The Prohibition Of supporting
confidence: 91%
“…Other studies using different methodologies show that having a religion influences opinions and experiences with sexuality [38][39][40][41][42] . These findings are similar to the results of our study, which show that greater frequency of participation in religious activities decreased the likelihood of sexual initiation at high school 37,[43][44][45][46][47][48][49][50] . Studies conducted in Africa have shown the opposite -that religiosity may actually increase the likelihood of sexual initiation at high school 51,52 -or that there was no association between religion and sexual initiation 53,54 .…”
Section: Discussion: Will Religious Discourse and The Prohibition Of supporting
confidence: 91%
“…Not only are Blacks and Hispanics at a disproportionate risk of contracting HIV (Centers for Disease Control and Prevention, 1992), they are also less knowledgeable about behaviors that increase one's risk of contracting HIV/AIDS (Miller, Turner, & Moses, 1990). Perhaps the greater likelihood of Blacks compared with whites making a general change in behavior may be a result of the lack of accurate knowledge among Black people concerning factors that predict an increased likelihood of transmission (Langer, Zimmerman, & McNeal, 1992). Perhaps the more behaviors that Blacks mistakenly believe will reduce their risk of HIV infection, the greater their general change score.…”
Section: Discussionmentioning
confidence: 95%
“…There is insufficient evidence to generalize our finding for either prosocial norms or spirituality as protective factors to other races/ethnicities. [152,46,100,138,[159][160][161][162][163][164][165][166][167][168][169][170][171][172][173] 12 c [38,153,161,163,167,174,175] [122,155,[188][189][190][191][192][193][194] 6 c [123,155,162,193,195] Use of contraception 2 a [196] 1 a [196] 9 ab [15,24,124,125,158,196] 4 c [56,…”
Section: Discussionmentioning
confidence: 99%